Humic acid removal by polyester nanofiltaration (NF) membrane synthesized from triethanolamine (TEOA) monomer - Fadzilah, Abdul Latif (2013)
Humic substances present in water sources affect the water quality causing undesirable color and taste, besides serving as food for bacterial growth in water distribution system. In order to treat this kind of natural organic matter, Nanofiltration (NF) Polyester membrane was produced by studying the effect of interfacial polymerization reaction time at constant monomer concentration. The thin film composite membranes were synthesized through interfacial polymerization with monomer concentration of 4% w/v of triethanolamine (TEOA) at different reaction time. The TEOA which was aqueous solution reacted with organic solution of trimesoylchloride (TMC) to produce new layer polyester on top of polyethersulfone (PES) microporous support. The thin film composite membrane was characterized in term of water flux, permeability and also solute rejection. The performances of NF membrane in terms of humic acid and NaCl rejection were increased as the reaction time increased. The performances in terms of flux and permeability showed that the flux and permeability were decreased as the reaction time increased. The longer reaction time had increased the layer thickness on the surface of the NF membrane which resulting the performances of the membranes.